Pericarditis as an onset of cancer - D. F. Mesitskaya; S. A. Panov; D. A. Andreev; A. N. Volovchenko; A. Sh. Dumikyan (Столичная издательская компания, 2023)
Pericarditis is an inflammation of the heart serous membrane of an infectious or non-infectious nature. Secondary pericardial effusion can be one of the few signs of cancer of the lung, pleura or breast in young people, while early treatment of the underlying pericarditis cause is the only factor influencing patient survival. We present a case report on a 28-year-old female patient who was hospitalized at the Sechenov University Cardiology Clinic for continuous recurrent pericarditis. During the examinations, end-stage lung adenocarcinoma was revealed, which for a long time was disguised as various diseases. Unfortunately, immunochemotherapy was not successful and the patient's condition was complicated by recurrent pulmonary embolism with progressive cardiopulmonary failure. A peculiarity of this case is the development of recurrent pericarditis in a young female patient with lung adenocarcinoma, which is difficult to diagnose using non-invasive examination methods. Long-term ineffective treatment of recurrent pericarditis is a reason for cancer suspicion in young patients.